Theoretical study of linker-type effect in carbazole–carbazole-based dyes on performances of dye-sensitized solar cells - Nawee Kungwan (2018)
© 2014, Springer-Verlag Berlin Heidelberg. Based on our recent report on a high overall conversion efficiency of the dye namely CCT3A exhibiting 96 % of the standard N719-based cell (Sudyoadsuk et al. in Eur J Org Chem, 23:5051–5063, 2013), a new series of metal-free organic donor–π–acceptor dyes are systematically further designed by an assistance of density functional theory (DFT) and time-dependent DFT (TD-DFT) methods. By taking carbazole–carbazole as a double-donor group and cyanoacrylic acid as an acceptor units, the π-linkers have been varied with different transporting moieties to investigate their potential performances in dye-sensitized solar cells (DSSCs) and evaluated through optimized geometries, charge distributions, electronic structures, simulated absorption spectra, and free energies of electron injection. The absorption spectrum of CCTA, one of our dyes in CCT3A series, was simulated by five different DFTs with various exchange–correlation functions to validate an appropriate functional prior to being employed as the functional of choice to investigate our new designed dyes. The long-range-corrected TD-CAM-B3LYP is found to provide the best results in predicting the λ max close to experimental data. The variation of π-linkers strongly affects the molecular orbital energy levels. The efficiencies of all dyes as sensitizers in DSSCs are also predicted by analyzing the important key parameters (the HOMO–LUMO energy gap (Δ H–L ), dipole moment change (Δμ), distance of charge transfer upon excitation from ground to excited state (D CT ), free energies of injection (ΔG inject ), and light-harvesting efficiencies). Our results suggest that the two carbazole–carbazole-based dyes containing thieno [3,2-b]thiophene and benzothiadiazole as the π-linker exhibit higher efficiencies than the existing CCTA dye.